Financial Ratio Analysis of the Regional Government of East Nusa Tenggara Province - Patty, Thadeus Fransesco Quelmo (Jurnal Economic Resource, 2025)
This study aims to analyze the financial ratios of the Nusa Tenggara Timur Provincial Government, including financial independence, effectiveness, efficiency, and regional revenue growth ratios. The method used is a quantitative, descriptive design, collecting secondary data from the NTT Provincial Government Financial Reports for the period 2020–2024. The results of the study indicate that although financial independence and revenue effectiveness ratios have increased, this province remains highly dependent on central government transfers. The efficiency ratio shows fairly good budget management, but further improvements are still needed. This study provides recommendations to increase local revenue and manage the budget more efficiently.